USM BROADENS COLLABORATION WITH INDUSTRY - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 17 June 2016 – Universiti Sains Malaysia (USM) continues to expand its network collaboration with the industry through the signing of a Memorandum of Understanding (MoU) with Macro Dimension Concrete Sdn Bhd (MDC), a company specialises in the production of concrete.